Learning the concept of adding and subtracting integers to Elementary School Students - Rohmawati, Desy Nur (Universitas Sebelas Maret, 2022)
This study aims to determine the learning of the concept of addition and subtraction in elementary school integers. Learning mathematics needs to understand the concept between addition and subtraction. With appropriate media and teaching materials, it is hoped that students will be able to understand the concept of addition and subtraction and be able to determine the operational results of addition. The concept of addition and subtraction that occurs, among others, in writing operation signs, such as plus (+), minus (-) and equal (=). The development of the times and technology has made students lazy in calculating numbers and lacking, because everything has been helped by calculators or via the internet. Students also consider mathematics as learning that makes students difficult so that many of the students do not like mathematics. The method used in the preparation of this article is a literature study. The results of the literature study found that learning media in the form of number cards, number lines, colored cards, and toy cars as well as teaching modules through the CTL approach and interactive learning videos were able to increase student activity and learning outcomes.